25 Years of IIF Time Series Forecasting: A Selective Review - Jan G. de Gooijer; Rob J. Hyndman (Tinbergen Institute, 2005)
We review the past 25 years of time series research that has been published in journals managed by the International Institute of Forecasters (Journal of Forecasting 1982-1985; International Journal of Forecasting 1985-2005). During this period, over one third of all papers_new published in these journals concerned time series forecasting. We also review highly influential works on time series forecasting that have been published elsewhere during this period. Enormous progress has been made in many areas, but we find that there are a large number of topics in need of further development. We conclude with comments on possible future research directions in this field.
Keywords: C22; C43; 330; Time-Series Models; Index Numbers and Aggregation; Zeitreihenanalyse; Prognoseverfahren